Reform of the Republic of Indonesia's State Police Through the Implementation of Big Data to Improve Efficiency, Transparency, and Accountability - Setiawan, Agung; Dudy, Aryadi Almau (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to analyze the potential application of Big Data within the Indonesian National Police (Polri) to improve the effectiveness, transparency, and accountability of reforms (the Arrangement of Authority and Law Enforcement Institutions). Using normative juridical research methods, this study identifies potential legal challenges, including issues of data privacy, human rights, and external oversight. The results indicate that although Big Data can improve the performance of the Indonesian National Police (Polri), its implementation requires in-depth regulatory adjustments to align with applicable legal principles.